"Calidad de vida en paciente hemodializado y con dialisis peritoneal del Hospital Víctor Lazarte Echegaray" - Delgado Rebaza, Milagros Geovanna (2014)
This research study is descriptive - comparative type, the purpose of the study was to identify the level of quality of life in hemodialysate and peritoneal dialysis patient of Victor Lazarte Echegaray Hospital. The study group consisted of a sample of 35 patients undergoing hemodialysis and 35 patients on peritoneal dialysis, selected according to inclusion criteria. Within this study took into account the notional units of Callista Roy and Dorothea Orem, with theories of adaptation and self-care respectively. For data collection , the interview method was used , applying the generic SF36 health questionnaire to determine the quality of life of patients undergoing hemodialysis and peritoneal dialysis, which consists of eight dimensions : physical functioning , role physical, bodily pain, general health, vitality, social functioning, role emotional and mental health. According to the results, it was found that patients undergoing hemodialysis achieved a higher percentage at the secondary level (48.6 percent) of quality of life, followed by the high level (40 percent) and low (11.4 percent); while comparatively patients in peritoneal dialysis treatment obtained a higher percentage in the low (45.7 percent) followed by high (34.3 percent) and medium (20 percent).